(untitled) (Bangkok, 2007)
The publication consists of four chapters that address flooding and saliniting management, livelihoods and resource use strategies, fisheries policy and competition for water use. The purpose of this content is to set out the background to how a transistion to sustainable development in the Mekong Region might be achived
Keywords: Sustainable development,Phát triển bền vững; Mekong region,Vùng Mêkông